2022
DOI: 10.3389/fpsyt.2022.1051235
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects and potential therapeutic implications of alarin in depression, and arguments on its receptor

Abstract: Alarin is a pleiotropic peptide involved in a multitude of putative biological activities, notably, it has a regulatory effect on depression-like behaviors. Although further elucidating research is needed, animal-based cumulative evidence has shown the antidepressant-like effects of alarin. In light of its regulatory role in depression, alarin could be used as a promising antidepressant in future treatment for depression. Nevertheless, the available information is still insufficient and the therapeutic relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 125 publications
0
1
0
Order By: Relevance
“…Beside the autonomic contribution of alarin it also has extra hypothalamic in uences. A recent study showed that alarin has regulatory effects in depression and may considered as a potential therapeutic target [9]. Another study demonstrated the cellular effect of alarin.…”
Section: Introductionmentioning
confidence: 99%
“…Beside the autonomic contribution of alarin it also has extra hypothalamic in uences. A recent study showed that alarin has regulatory effects in depression and may considered as a potential therapeutic target [9]. Another study demonstrated the cellular effect of alarin.…”
Section: Introductionmentioning
confidence: 99%